2020
DOI: 10.1001/jamasurg.2019.4908
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Mortality With Postoperative Myocardial Infarction After Major Vascular Surgery Despite Use of Evidence-Based Therapies

Abstract: IMPORTANCE Patients undergoing vascular surgery are at high risk of postoperative myocardial infarction (POMI). Postoperative myocardial infarction is independently associated with significant risk of in-hospital mortality.OBJECTIVE To examine the association of patient and procedural characteristics with the risk of POMI after vascular surgery and determine the association of evidence-based therapies with longer-term outcomes. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study of prospectively coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…[ 15 ] Recent evidence, however, stated a 37.4% incidence of 1-year mortality in patients who had PMI after undergoing high-risk vascular surgery. [ 30 ] Although excluding thoracoabdominal surgery from analysis, they had included carotid artery procedures, peripheral artery surgeries, and endovascular aortic aneurysm repair procedures, which are specifically known for their low risk of PMI. The elevated risk in our cohort can thus be associated with the focussed analysis of patients with CAD and the inclusion of more morbid surgeries involving the thoracic aorta.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Recent evidence, however, stated a 37.4% incidence of 1-year mortality in patients who had PMI after undergoing high-risk vascular surgery. [ 30 ] Although excluding thoracoabdominal surgery from analysis, they had included carotid artery procedures, peripheral artery surgeries, and endovascular aortic aneurysm repair procedures, which are specifically known for their low risk of PMI. The elevated risk in our cohort can thus be associated with the focussed analysis of patients with CAD and the inclusion of more morbid surgeries involving the thoracic aorta.…”
Section: Discussionmentioning
confidence: 99%
“…32 Beaulieu et al studied the risk of postoperative myocardial infarction after major vascular surgery and found a high risk of AMI following peripheral bypass surgery, with approximately 49% having DM among those suffering from AMI postoperatively. 7 Two randomized controlled trials 33,34 have shown that low-dose rivaroxaban taken twice a day plus aspirin once a day reduced major adverse cardiovascular and limb events when compared with ASA alone; therefore, it is of great importance to consider that patients are treated with the best medical therapy not only after the procedure but perhaps at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…5 Individuals with both DM and PAD have a more distal distribution of the arterial disease, and tend to have more significant comorbidities. 6 In view of these factors, minimal invasive endovascular therapy for CLTI among patients with DM might induce less myocardial stress 7 compared to open surgery, and therefore be more beneficial to achieve higher amputation-free survival. Indeed, endovascular therapy was associated with a lower risk of mortality in patients with type 2 diabetes compared to those without DM among patients with infrainguinal CLTI.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Open aortic procedures are especially associated with a higher risk of postoperative myocardial infarction, which is in turn associated with up to 650% increased risk of 1-year mortality. 9,10 Although postoperative stroke in noncarotid vascular surgery is rare (< 1%), it is associated with a significantly increased risk of 30-day perioperative mortality (approximately three to sixfold increase). 11,12 Postoperative arrhythmias affect a large percentage of patients undergoing noncardiac surgery, with the incidence of 7-8% -most frequently atrial fibrillation (~4.4%).…”
Section: Introductionmentioning
confidence: 99%